That bandit of the Unnamed (and other ugly mugs of the 19th century) (Altre Modernità, 2023)
A particular form of contagion, closely linked to the contagion of ideas, is the contagion of the imagination. This contribution investigates how the stereotype of the bandit (the so-called bandit mania) was so widespread in the 19th century that it secretly penetrated even into the Promessi sposi ‘The Betrothed’, i.e. one of the most carefully controlled and most original writings of the 19th-century novelistic production in Italy. In particular, in the  “Schizzo più ampio della figura dell’innominato” 'Wider sketch of the figure of the unnamed' (present among the so-called 'Loose leaves', which refer to the intermediate phase between Fermo e Lucia and the Ventisettana), the character's trajectory seems to take a slightly different path to the one everyone remembers: he who will be, in the final version, a 'tyrant' in a titanic and tragic sense, as well as a powerful icon of conversion, is here still the metaphorical 'tyrant' (i.e. outlaw, bandit) of an urban microcosm of the underworld.
Keywords: banditti mania; Manzoni; The Betrothed; the Unnamed; contagion of immagination